The Impact of Territorial Branding on Customer Attitude towards « the made in Morocco » Brands: Case of Agri-Food Products. - IHIS AMINA; NAOUI Fouad (African Scientific Journal, 2024)
Abstract In the face of global market challenges, developing countries like Morocco strive to protect domestic industries while engaging in international trade. This study proposes territorial branding strategies to enhance consumer attitudes towards locally made agri food products in the Moroccan market. Drawing on theoretical frameworks from territorial branding and consumer behavior literature, this research explores how territorial branding initiatives influence Moroccan consumer attitudes towards agri food product quality, authenticity, and trust, fostering a "Buy Domestic" mindset. Despite limited empirical evidence, theoretical discussions underscore the role of territorial branding in safeguarding local producers from imports. By prioritizing tailored territorial branding efforts, policymakers can promote economic protectionism and empower local producers. Keywords Territorial Branding, Consumer Attitudes, Buy Domestic, Moroccan Market, Economic Protectionism, Agrifood Products.